2019
DOI: 10.1038/s41417-018-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

High expression of UBE2T predicts poor prognosis and survival in multiple myeloma

Abstract: Multiple myeloma (MM) is one of hematological malignancies, characterized by malignant proliferation of plasma cells. Biomarkers play an important role in evaluating the development and prognosis of MM. Ubiquitin-conjugating enzyme E2T (UBE2T) is served to connect with particular E3 ubiquitin ligase to degraded-related substrates, contributing to DNA repair in the Fanconi anemia pathway. Also, numerous evidences reported that UBE2T is closely related to cell proliferation and carcinogenesis. However, the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Therefore, UBE2T may be considered as a potential drug target for patients with gallbladder cancer. Numerous studies demonstrated that UBE2T is overexpressed in various types of cancer, including multiple myeloma ( 20 ), hepatocellular carcinoma ( 54 ), bladder cancer ( 24 ) and osteosarcoma ( 25 ), suggesting that it may be an attractive drug target. The results from the present study indicated that UBE2T may be considered as a prognostic factor for patients with gallbladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, UBE2T may be considered as a potential drug target for patients with gallbladder cancer. Numerous studies demonstrated that UBE2T is overexpressed in various types of cancer, including multiple myeloma ( 20 ), hepatocellular carcinoma ( 54 ), bladder cancer ( 24 ) and osteosarcoma ( 25 ), suggesting that it may be an attractive drug target. The results from the present study indicated that UBE2T may be considered as a prognostic factor for patients with gallbladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Among all hub genes identified, ubiquitin conjugating enzyme E2T (UBE2T) was firstly highlighted in a patient with Fanconi anemia (18). It has been reported that hypoxia may disrupt the Fanconi anemia pathway and sensitize tumor cells to chemotherapy by regulating UBE2T (19,20). Furthermore, UBE2T overexpression is associated with poor prognosis of patients with various types of cancer, including breast cancer and multiple myeloma (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…For example, UBE2T is remarkably upregulated in MM cells, especially in the early stage. UBE2T level is signi cantly associated with IgG serotype of MM and UBE2T upregulation predicts poor prognosis, including OS and event-free survival time, of patients with MM [29]. Furthermore, UBE2T is upregulated in gastric cancer tissues and cells, positively associated with poor differentiation, advanced T stage, and short OS time in patients with gastric cancer [9,10].…”
Section: Discussionmentioning
confidence: 98%
“…In addition to DNA crosslinkers, the FA pathway also confers resistance to DNA alkylating agents in glioma [110]. Alongside FA-mediated drug resistance are observations that FANCA and FANCT/UBE2T correlate with poor prognosis and survival of cancer patients [111,112]. These pre-clinical data highlight the need for development of FA targeted drugs in circumstances where chemotherapy resistance emerges as a result of elevated FA pathway expression and function.…”
Section: Association Of the Fa Pathway With Drug Resistancementioning
confidence: 99%